2003
DOI: 10.1029/2002gb001987
|View full text |Cite
|
Sign up to set email alerts
|

Eddy‐driven sources and sinks of nutrients in the upper ocean: Results from a 0.1° resolution model of the North Atlantic

Abstract: [1] A nitrate-based model of new production is incorporated into eddy-resolving (0.1°) simulations of the North Atlantic. The biological model consists of light and nutrient limited production within the euphotic zone and relaxation of the nitrate field to climatology below. Sensitivity of the solutions to the parameters of the biological model is assessed in a series of simulations. Model skill is quantitatively evaluated with observations using an objective error metric; simulated new production falls within… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
199
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 221 publications
(213 citation statements)
references
References 112 publications
(165 reference statements)
12
199
2
Order By: Relevance
“…While previous model studies showed that eddies actually decrease nutrient availability in the Labrador Sea (McGillicuddy et al, 2003), which should adversely affect a bloom, our results are contrary. A third explanation for our results and those of McGillicuddy et al (2003) could be that eddies in this region do not supply additional nutrients, but rather aid in the haline stratification of the region, since these eddies tend to be fresh at the surface (Frajka-Williams et al, 2009).…”
Section: Discussioncontrasting
confidence: 57%
See 2 more Smart Citations
“…While previous model studies showed that eddies actually decrease nutrient availability in the Labrador Sea (McGillicuddy et al, 2003), which should adversely affect a bloom, our results are contrary. A third explanation for our results and those of McGillicuddy et al (2003) could be that eddies in this region do not supply additional nutrients, but rather aid in the haline stratification of the region, since these eddies tend to be fresh at the surface (Frajka-Williams et al, 2009).…”
Section: Discussioncontrasting
confidence: 57%
“…A third explanation for our results and those of McGillicuddy et al (2003) could be that eddies in this region do not supply additional nutrients, but rather aid in the haline stratification of the region, since these eddies tend to be fresh at the surface (Frajka-Williams et al, 2009).…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Heat and salt transports can be calculated using currents, sea surface temperature (SST), and sea surface salinity. Ocean eddies are an important source of upwelling, a process that brings nutrient-rich deep waters to the surface to supply the food chain [McGillicuddy et al, 2003].…”
Section: How Do Ocean Currents Impact Our Lives?mentioning
confidence: 99%
“…At the same time, there is evidence that horizontal physical processes could play a role, particularly in the northern subtropical gyre or "intergyre" region of the North Atlantic [Williams and Follows, 1998;Dutkiewicz et al 2001;Follows and Dutkiewicz 2002;Oschlies 2002;McGillicuddy et al 2003;.…”
Section: Introductionmentioning
confidence: 99%